Acinar Cell-Derived Extracellular Vesicle MiRNA-183-5p Aggravates Acute Pancreatitis by Promoting M1 Macrophage Polarization Through Downregulation of FoxO1 - Tang, De-sheng; Cao, Feng; Yan, Chang-sheng; Cui, Ji-tao; Guo, Xiao-yu; Cheng, Long; Li, Le; Li, Yi-long; Ma, Jia-min; Fang, Kun; Gao, Lei; Ren, Nian-sheng; et al. (Frontiers in Immunology, 2022)
Acute pancreatitis (AP) is a common cause of a clinically acute abdomen. Crosstalk between acinar cells and leukocytes (especially macrophages) plays an important role in the development of AP. However, the mechanism mediating the interaction between acinar cells and macrophages is still unclear. This study was performed to explore the role of acinar cell extracellular vesicles (EVs) in the crosstalk between acinar cells and macrophages involved in the pathogenesis of AP. EVs derived from caerulein-treated acinar cells induced macrophage infiltration and aggravated pancreatitis in an AP rat model. Further research showed that acinar cell-derived EV miR-183-5p led to M1 macrophage polarization by downregulating forkhead box protein O1 (FoxO1), and a dual-luciferase reporter assay confirmed that FoxO1 was directly inhibited by miR-183-5p. In addition, acinar cell-derived EV miR-183-5p reduced macrophage phagocytosis. Acinar cell-derived EV miR-183-5p promoted the pancreatic infiltration of M1 macrophages and increased local and systemic damage in vivo. Subsequently, miR-183-5p overexpression in macrophages induced acinar cell damage and trypsin activation, thus further exacerbating the disease. In clinical samples, elevated miR-183-5p levels were detected in serum EVs and positively correlated with the severity of AP. EV miR-183-5p might play an important role in the development of AP by facilitating M1 macrophage polarization, providing a new insight into the diagnosis and targeted management of pancreatitis. Graphical abstract of the present study. In our caerulein-induced AP model, miR-183-5p was upregulated in injured acinar cells and transported by EVs to macrophages. miR-183-5p could induce M1 macrophage polarization through downregulation of FoxO1 and the release of inflammatory cytokines, which could aggravate AP-related injuries. Therefore, a vicious cycle might exist between injured ACs and M1 macrophage polarization, which is fulfilled by EV-transported miR-183-5p, leading to sustainable and progressive AP-related injuries.